PENGARUH LATIHAN TENDANGAN LURUS TANPA BEBAN TERHADAP KECEPATAN TENDANGAN ATLET PENCAK SILAT PUTRI PERGURUAN TAPAK SUCI PEKANBARU - Ainul Husni; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is that the speed of kick is still lacking, it is seen from various tests and official matches and this is one of the factors causing defeat. This type of research is a type of experimental research to see the effects of this form of exercise. The purpose of this research is to see the effect of straight kick without load exercise on speed of kick athletes the martial art female group Tapak suci of Pekanbaru. Population in this research is athletes the martial art female group Tapak suci of Pekanbaru which amounted to 6 people. The sampling technique is by using total sampling, in which the total population is sampled. Technique of taking data obtained from pre-test and posttest. Instrument in this research using Test of kick punching bag in 10 seconds as tool to measure speed of kick skill. The analysis was performed using t-test. Based on the analysis and discussion of data, it can be concluded that there is a significant influence of straight kick without load exercises on speed of kick athletes the martial art female group Tapak suci of Pekanbaru as evidenced by Thitung of 8,333 and Ttabel 1,943. Means Thitung> Ttable. At ɑ = 0.05 level.Key Words: Straight Kick Without Load, Speed of Kick